Trauma Arrest and Spinal Injury in a 3-Year-Old Girl. Issue 12 (December 2017) - High, Kevin; Walsh, Michele; Kidd, Rebecca
Abstract : Abstract: Management of an acutely injured pediatric patient with multiple traumas is a common challenge facing clinicians in pediatric emergency care. Blunt trauma is more common in the pediatric population with motor vehicle accidents being the most common cause of injury. Spinal injury, especially in young children, is only seen in 1% to 2% of cases and can be lethal. It is incumbent upon clinicians to be able to meet the challenges of patient management including airway management, providing hemodynamic support, and addressing potentially reversible causes of arrest while recognizing presenting symptoms of spinal injury. This case presents a child in trauma arrest after a motor vehicle crash requiring advanced interventions, diagnostics, and support. Her clinical course is described and reveals a complete distraction of the cervical and thoracic spine. This case illustrates pathology and management along with the importance of proper management and interventions by pediatric emergency clinicians to manage the patient and attempt to maximize the patient's outcome.